Bifunctional nickel oxide-based nanosheets for highly efficient overall urea splitting. Issue 46 (20th May 2019) - Wu, Fengchi; Ou, Gang; Yang, Jun; Li, Henan; Gao, Yanxia; Chen, Fuming; Wang, Ye; Shi, Yumeng
Abstract : 2D Ni0.9 Fe0.1 O x nanosheet assembled porous and hollow microspheres were synthesized for efficient overall urea splitting. Abstract : Porous and hollow Ni0.9 Fe0.1 O x microspheres assembled from 2D nanosheets exhibit excellent bifunctional activity for both urea oxidation reaction and hydrogen evolution reaction, in which the potential for overall urea splitting is 1.455 V at 10 mA cm −2 .